JRDM 2020
DOI: 10.7176/jrdm/63-05
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study Between Gender Bias in Household Water Conservation and Management in Commune of Pelengana

Abstract: Highlighting the practice of water conservation (PWC) is a safe way to accomplish water savings. Nevertheless, parameters affecting behavior change linked to water use keep uncertain. In this study, 467 residents (female: 272; male: 195) from three villages situated in the commune of Pelengana in Segou, Mali were investigated in order to analyze the effects of awareness, perceptions and individual water-use patterns control on PWC, and also the influence of gender on inhabitants' PWC. One-way analysis of varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
3
1
1
Order By: Relevance
“…There was no significant difference in their harvest of rainwater for use between male respondents (M=3.5484, SD = 1.10157) and female respondents (M=3.5325, SD =1.09775); t (647) = 0.178, p = 0.859. The finding made in this study runs contrary to what is established by Diakite et al (2020), where gender was a demographic characteristic that impacted water conservation, as women were found to have greater levels of water conservation practices. But in Malik et al (2021) men were observed to have a higher level of water conservation practices.…”
Section: Common Domestic Water Conservation Practices In the Fctcontrasting
confidence: 99%
See 1 more Smart Citation
“…There was no significant difference in their harvest of rainwater for use between male respondents (M=3.5484, SD = 1.10157) and female respondents (M=3.5325, SD =1.09775); t (647) = 0.178, p = 0.859. The finding made in this study runs contrary to what is established by Diakite et al (2020), where gender was a demographic characteristic that impacted water conservation, as women were found to have greater levels of water conservation practices. But in Malik et al (2021) men were observed to have a higher level of water conservation practices.…”
Section: Common Domestic Water Conservation Practices In the Fctcontrasting
confidence: 99%
“…But in Malik et al (2021) men were observed to have a higher level of water conservation practices. According to Garcetti and Kevany (2013) cited in Diakite et al (2020), women and girls feel the impact of water scarcity more (particularly in rural areas), as they are usually saddled with the responsibility of collecting and transporting water in such situations, the outcome of this study which shows that there are insignificant differences in the level of domestic water conservation practices by the male and female respondents does imply that conservation practices bear equal importance to both genders. Women who are usually more involved in household chores and use water in the process; and men who are the major decision-makers in homes are both actively contributing to domestic water conservation in similar measures.…”
Section: Common Domestic Water Conservation Practices In the Fctmentioning
confidence: 55%
“…The identified low participation level to conserve water in Singida Municipality is consistent with different academic studies conducted in different areas. The study findings of Diakite & Amadou, (2020) in Mali reported that many respondents were aware of WCPs but had low participation in conservation practices. The study by Kusena et al, (2016)in Zimbabwe assessing public participation in water conservation found that only a few respondents participate in conserving water due to limited involvement in decisionmaking and conservation practice literacy.…”
Section: Discussionmentioning
confidence: 91%
“…The level and extent of participation in water conservation by the community and households in different areas is positively and negatively affected by many factors. According to Diakite & Amadou, (2020)with the help of ANOVA, in a comparative study between gender bias in household water conservation and management using a sample size of 467 residents in Mali, males had low participation as compared to females in water conservation practices. The main reason for the good participation of females was to reduce water bills and for males, water scarcity was a big concern, but in general awareness, perception, and community involvement in decision-making were observed to be the determinants of water use control.…”
Section: Household Participation In Conserving Water Resourcesmentioning
confidence: 99%
“…Con esta información se genera la Tabla 5, así mismo, se analiza el resultado en la gráfica de valoración del nivel piezométrico determinado al momento de aplicar el método de elemento finito (Diakite, 2020).…”
Section: Tabla 5 Datos De Proyecto Adap [Mi] (2 Días)unclassified